Non-Traumatic Acute Subdural Hemorrhage Due To Cranial Venous Hypertension. Issue 1 (March 2019) - Orde, Matthew M.
Acute subdural hemorrhage is typically associated with a history of head trauma, and as such it is a finding with significant potential medicolegal consequences. In this article, 37 adult and post-infantile pediatric sudden death autopsy cases with small volume ("thin film" or "smear") acute subdural hemorrhage are presented—in which there is either no further evidence of head trauma or only features of minor head injury. The possible underlying pathophysiological mechanisms are explored, and it is concluded that a common thread in many of these cases is likely to have been cranial venous hypertension at around the time of death. These findings may have implications in instances where small volume subdural hemorrhage is identified in the absence of other evidence of significant head injury.